Nők a városi szegénységben Magyarországon: Szobalányok és dolgozó nők a munkaerőpiacon 1945 előtt - Czibere, Ibolya (METSZETEK Társadalomtudományi Folyóirat, 2013)
The economic and social transition caused by the industrial revolution at the end of the 19th century has brought about several changes in Hungary. The development of infrastructure and transportation enabled women to access new job opportunities, to abandon traditional communities and to try new ways of living. In Hungary, keeping maids continued to be a social custom and even between the two world wars affected a large number of people.